Lightning performance analysis of a grid-connected solar photovoltaic system - Zaini, Nur Hazirah (2019)
The Malaysian government implemented the Feed-in-Tariff (FiT) and the Net Energy Metering (NEM) programme to accelerate the deployment of renewable energy, and encourage the production of clean green energy approaches like the solar PV system. Malaysia is a good fit for the deployment of solar PV system due its high daily radiation but unfortunately, the solar PV farm in Malaysia is highly susceptible to lightning strikes considering most solar PV farms are installed in wide-open areas that consequently attract lightning. This leads to very considerable repair costs, replacement of parts and the interruption of power supply to a large number of consumers. Therefore, the installation of a lightning protection system (LPS) in the solar PV farm is imperative to ensure the protection of all electronic equipment from damage due to lightning strikes. However, no specific standard or guideline is available for LPS, specifically for the solar PV system. Currently, installation of LPS for the solar PV system refers to Malaysian standard, which include MS 1837, MS IEC 62305, and technical document CLC/TS 50539-12 which provide just a brief overview. Hence, this study was conducted to determine a guideline and recommend suitable installation of LPS especially the surge protective device (SPD). This study provides a comprehensive model of a grid-connected solar PV farm system in PSCAD software consisting of a typical arrangement of solar PV modules, inverter, and transformer to observe the lightning effect and to coordinate an appropriate LPS. Depending on the location of the solar PV farm, engineers can obtain information on the peak current and median current of the site from the lightning location system (LLS). A statistical analysis of lightning peak current was performed and the findings revealed that the solar PV farm at Puchong Gateway have a total of 8788 strikes lightning strikes. In the simulation, the lightning strikes were applied without any LPS installed at the solar PV farm to show the consequences if the design engineers and developer neglect the installation of an LPS. In addition, the SPD rating was also established by comparing the SPD Type I and SPD Type II. Results obtained were utilised in this study to appropriately assign an SPD in the solar PV farm. One the DC side a single SPD installed near inverter was not enough to protect the solar PV even though the cable length is less than 10 m. Furthermore, a single SPD installed on the AC side positioned near the origin of installation for cable length less than 10 m was also not enough to protect the inverter from high transient voltage and current cause by lightning. Hence, a step of SPD installation and a recommendation of SPD installations for a solar PV farm were made in the form of guidelines to designers in order to decide on the placement, number and suitable rating of SPDs to be installed for full protection of all equipment. Findings of this study will help improve the existing standards and assist engineers to design an integral part of the installation of LPS for grid-connected solar PV farm system. Ultimately, it will significantly reduce the expensive cost of repairing damages caused by lightning strikes and enhance the efficiency of the power supply.